Analysis of the Impact of Artificial Intelligence (AI) Technology as a Predictive Tool in Capital Budgeting: Opportunities and Challenges in the Digital Era - Fitra Amalia Jafar; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2025)
The rapid advancement of digital technology today has driven significant transformation in various aspects of business operations, including financial decision-making within companies. This study focuses on examining the effects of using AI technology as a predictive tool in capital planning, as well as identifying the opportunities and challenges faced by companies in today's digital age. This study is a descriptive study using secondary quantitative methods, aimed at explaining phenomena in a structured and fact-based manner using existing data and information. The main findings of this study indicate that the integration of Artificial Intelligence (AI) in financial management can facilitate the examination of past data and market developments directly, as well as generate more accurate and effective predictions. However, the lack of transparency in this system raises significant concerns regarding its use in critical fields such as finance and healthcare, where transparency in decision-making processes is of utmost importance. Through this research, it can be concluded that the use of AI technology can provide opportunities for companies to manage data in planning capital budgeting, but behind this convenience, companies must also face challenges related to data security and various other aspects in implementing AI technology in the current technological era.